PENGUATAN FUNGSI PENGAWASAN DALAM SISTEM PENEGAKAN HUKUM SEBAGAI UPAYA MENEKAN JUDICIAL CORRUPTION - Agus Velliana Yosephus (Faculty of Law, Universitas Diponegoro, 2014)
This study aims to analyze about the existence or the judicial mafia practices in Indonesia. In enforcing the law, should not be ruled out in the Integrated Criminal Justice System (SPPT). This system as a unity between the police, prosecutors and courts as sub-systems. The research found that the duties are supervisory agencies of the criminal justice system , namely the institution's internal control and external oversight agency, found also that the strengthening of the supervisory function of law enforcement in the criminal justice system is very weak due to the modus operandi of the mafia practice of law was made during the investigation at the level of the police and prosecution at the level of the prosecutor.